Evaluation of Mono and Hybrid Nanofluids in MQL Milling of Ti-6Al-4V: Machining Performance, Surface Integrity and Sustainability - Aydin, Alper; Sagdic, Omer Faruk; Yucel, Muhammed; Yapan, Yusuf Furkan; Kizilkaya, Hakan Zafer; Uysal, Alper (KOREAN SOC PRECISION ENG, 2026)
Ti-6Al-4V alloy's machining poses considerable challenges owing to its low thermal conductivity, high strength, and interaction with cutting tools, leading to issues related to machining performance and surface quality. To address these challenges, in the presented study, the minimum quantity lubrication method using the hBN/MWCNT hybrid nanofluid (HNMQL) was used for the first time in the milling of Ti-6Al-4V, and the machining response was evaluated regarding cutting force, feed force, cutting temperature and cutting tool condition, the surface integrity was evaluated regarding surface roughness, surface topography, microhardness, and microstructure, and the sustainability was evaluated regarding totaal carbon emissions and total machining cost. In comparison to the dry-cutting, the HNMQL approach improved the cutting force, feed force, cutting temperature, surface roughness, surface topography, total carbon emissions, and total machining cost emissions by 63.5%, 87%, 65.8%, 65.8%, 74.7%, 27.8% and 24.6% respectively. In addition, it prevented the wear and damage mechanisms in the cutting tool. The HNMQL cutting condition, which provided the lowest microhardness, showed 16.4% less work hardening than the dry cutting condition, which provided the highest microhardness, and the results were also confirmed by the microstructural changes. As a result, it was realized that addressing the difficulties in machining the Ti-6Al-4V using the hBN/MWCNT HNMQL method improves the machining performance, surface/sub-surface properties, and environmental impact.
Keywords: Ti-6Al-4V; Hybrid nanofluid; Machining performance; Surface integrity; Sustainability assessment; MINIMUM QUANTITY LUBRICATION; TOOL WEAR; NANOPARTICLES; MECHANISM; FLUIDS; Science & Technology - Other Topics; Engineering